Primary health care in the Czech Republic: brief history and current issues - Holcik, J; Koupilova, I (International journal of integrated care, 2000)
The objective of this paper is to describe the recent history, current situation and perspectives for further development of the integrated system of primary care in the Czech Republic. The role of primary care in the whole health care system is discussed and new initiatives aimed at strengthening and integrating primary care are outlined. Changes brought about by the recent reform processes are generally seen as favourable, however, a lack of integration of health services under the current system is causing various kinds of problems. A new strategy for development of primary care in the Czech Republic encourages integration of care and defines primary care as co-ordinated and complex care provided at the level of the first contact of an individual with the health care system.